ISSUES OF IMPROVEMENT OF CHAPTER 11 "ENVIRONMENTAL CRIMES" OF THE CRIMINAL CODE OF KAZAKHSTAN (Journal of actual problems of jurisprudence, 2019)
This article is dedicated to problem of criminal responsibility for ecological crimes. There are offers on improvement of criminallegislation of Republic of Kazakhstan in this area are maded.